The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1992
DOI: 10.1159/000186838
|View full text |Cite
|
Sign up to set email alerts
|

Low Urine Citrate Excretion as Main Risk Factor for Recurrent Calcium Oxalate Nephrolithiasis in Males

Abstract: To better define the relative role of metabolic factors in the recurrence of stone formation, we studied the 24-hour urinary excretion of calcium (uCa), citrate (uCit), oxalic acid (uOx) and uric acid (uUa) in 73 male patients with primary calcium oxalate urolithiasis. According to the episodes of stone formation per year, we identified 51 recurrent stone formers (RSF) and 22 single stone formers (SSF). 20 normal adult males constituted the control group (C). uCa and uOx were higher in RSF than in C, but quite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
12
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 21 publications
(27 reference statements)
6
12
0
Order By: Relevance
“…In this study, we also observed a high incidence of calcium oxalate stone: 70.8% in FSF patients and 59.4% in RSF patients. Hypocitraturia was the most common abnormality in this study in both groups, consistent with previous reports [5,17]. Although our data indicate that on the basis of urinary citrate levels, patients with recurrent stone formation cannot be distinguished from patients with 1 episode only, we can assume that urinary citrate is an important risk factor for stone disease.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In this study, we also observed a high incidence of calcium oxalate stone: 70.8% in FSF patients and 59.4% in RSF patients. Hypocitraturia was the most common abnormality in this study in both groups, consistent with previous reports [5,17]. Although our data indicate that on the basis of urinary citrate levels, patients with recurrent stone formation cannot be distinguished from patients with 1 episode only, we can assume that urinary citrate is an important risk factor for stone disease.…”
Section: Discussionsupporting
confidence: 93%
“…Despite the introduction of non-invasive techniques for the removal of stones and the identification of several metabolic factors responsible for stone formation [4][5][6], stone recurrence continues to be a significant clinical problem [16]. About 80% of urolithiasis patients have been reported to have calcium oxalate stones [11].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it may not be the absolute urinary calcium or citrate concentrations that determine the risk of stone formation but rather the relative excess of calcium over citrate. Similarly, Cupisti et al (26) found that stone formers had higher urinary calcium excretion and low citrate excretion, which was more marked in recurrent stone formers. As early as 1976, Welshman and McGeown (14) had found urinary calcium/citrate ratio to be different in normal adult subjects and stone formers but found a difference between the two genders.…”
Section: Discussionmentioning
confidence: 86%
“…Urinary citrate is an inhibitor of crystallization of calcium salts in urine, and studies have linked lower levels of urinary citrate excretion to increased calcium oxalate stone risk [30]. Urinary citrate levels of <2.0 mmol/day in males and <2.5 mmol/day in females are considered abnormal.…”
Section: Investigation Of Renal Stonesmentioning
confidence: 99%